Pemberdayaan Kader Cilik dalam Peningkatan Pengetahuan, Sikap dan Perilaku Jajan Anak Sekolah - Oslida Martony (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the knowledge, attitudes, and behavior of school children snacks before and after counseling related to the empowerment of cadres in schools at Muhammadiyah Lubuk Pakam Elementary School. This research method is a correlative study using a cross-sectional design. The results of the static test show that the value of p = 0.00 <0.05 means that there are significant differences between the knowledge, attitudes, and behavior of Muhammadiyah students' snacks in choosing healthy meals and snacks that contain hazardous ingredients after empowerment by young cadres, In conclusion, the counseling method is very influential in significantly increasing the knowledge, attitudes, and behavior of school children at SD Muhammadiyah Lubuk Pakam. Keywords: Snack for School Children, Young Cadres, Knowledge, Behavior, Attitude